The Mediating Role of Purchase Intention between Product Display, Price Perception, and Purchasing Decisions in Retail Pharmacies - Wa Ode Mirawanti; Ruslin Ruslin; Asriullah Jabar; Henny Kasmawati; Fery Indradewi Armadany; Adryan Fristiohady (GLOBAL HEALTH SCIENCE GROUP, 2026)
The transformation of retail pharmacies into modern retail environments has intensified competition, making marketing strategies such as product display and pricing increasingly important in influencing consumer purchasing behavior. Objective: This study aims to analyze the effect of product display and price perception on purchasing decisions through purchase intention in modern retail pharmacies. This quantitative study employed a cross-sectional design involving 180 respondents from a modern retail pharmacy (Apotek A) in Kendari City. Data were collected using structured questionnaires selected using purposive sampling from a modern retail pharmacy (Apotek A) in Kendari City. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Measurement model (outer model) and structural model (inner model) evaluations were conducted to assess validity, reliability, and hypothesis testing. The results indicate that product display and price perception have significant positive effects on purchase intention. Purchase intention, in turn, significantly influences purchasing decisions and mediates the relationship between product display, price perception, and purchasing decisions. All constructs demonstrated adequate validity and reliability. Effective product display and favorable price perception enhance consumers’ purchase intentions, leading to higher purchasing decisions in retail pharmacies. These findings highlight the strategic importance of retail-oriented management practices in modern pharmacies.